Taxpayer perceptions of the Coretax System: A TAM–ISSM approach - Wibowo, Hari Tri; Mariani, Dina (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2026)
This study seeks to examine taxpayer perceptions of the Coretax System utilizing the Technology Acceptance Model (TAM) and the Information Systems Success Model (ISSM). Employing a qualitative research approach, this investigation adopts a phenomenological method and conducts semi-structured interviews with 11 users of the Coretax system. The findings indicate that Coretax is perceived as user-friendly and advantageous in enhancing the efficiency of tax reporting and payment processes. The quality of the system, service, and information is generally regarded as satisfactory; however, technical challenges, limited outreach, and slow service responses persist. The primary impetus for utilizing Coretax is the regulatory mandate necessitating its use in tax assessments. While Coretax holds potential for improving tax compliance, this potential is not fully realized because of system instability. The conditions facilitating the Coretax system and governmental support are deemed adequate, albeit hindered by limited outreach and training provided by the government or the Directorate General of Taxes (DJP). The availability of technology did not significantly influence the utilization of the Coretax system. There is no resistance to change, as the Coretax system is perceived as more accessible and integrated, and a positive perception of its security.